FORMULASI DAN PENINGKATAN MUTU MASKER WAJAH DARI BIJI KAKAO NON FERMENTASI DENGAN PENAMBAHAN RUMPUT LAUT - Wahyuni, Wahyuni; Lullung, Alfrida; Asriati, Dyah Wuri (Jurnal Industri Hasil Perkebunan, 2016)
A research on formulation and quality improvement of non fermented cocoa bean face maskswith seaweed addition has been done. The purpase of this study was to improve the quality of nonfermented of cocoa bean face mask with seaweed addition to obtaine the most optimal stability. Bykeeping all other ingredients composition constant, the seaweed addition was varied (15, 20, 25) grams,and propylene glycol (10, 7.5, 5) grams refers to a preliminary study of 2.5 grams cocoa paste used for250 grams creams receipe. The results showed that non fermented cocoa beans can be processed asraw materials for the skin care health products (face mask cream). Face mask cream stability test of allformulas with concentrations of 15 g of seaweed, 10 propylene glycol showed a better quality compliedwith cosmetics qualification as face mask cream compared with other compositions on centrifuges test,homogeneity, freeze thaw,physical stability, pH (7.77) and test viscosity (1.35) x103cp. In vitro toxicity testof seaweed face mask cream did not cause irritation effects on the skin.Keywords: Face mask cream, cocoa paste, seaweed, stability, skin irritation